History of menstrual disorders associated with gestational diabetes mellitus - Shahnaz Barat; Zinatossadat Bouzari; Shahla Yazdani; Rahil Moslemi; Karimollah Hajian-Tilaki (Caspian Journal of Reproductive Medicine, 2016)
Background: Despite the fact that many studies have been published about the risk factors associated with gestational diabetes mellitus, its prevalence remains high. The aim of this study was to examine the relationship between the history of irregular menses and gestational diabetes mellitus among pregnant women.